AN ANALYSIS OF GRAMMATICAL ERRORS IN WRITING RECOUNT TEXT AT THE FIRST YEAR CLASSES OF ENGLISH DEPARTMENT - Martiarini, Elyza; Candra, Eva Nurul (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2019)
The objective of this research is to find out and analyze the types of error made by students at the first-year classes in writing a recount text. The methodology of the research used is qualitative methods and the research design is a case study. Moreover, the writers chose the first-year classes students of English Department and observed 40 students. The writers used a written test to gain the data about error in writing a recount text. Based on the analysis of students? recount text writing, there were several mistakes made by the students, with the total number of percentages was 76%. Of these, 76% errors including 15% errors of irregular verb usage, 12% errors of regular verb, and the type of error most often done by the students was 32% errors of word choice, 2% errors of omission, 3% errors of auxiliary verb, 5% errors of intralingual transfer, 2% errors of adverb, error of misordering was 5%, and error of unclear meaning was only 2%. The number errors of be was 17%, and the use of personal pronoun errors was 7%.